Validity Evidences of the Internalized Homophobia Scale for Brazilian Gays and Lesbians - Aline Nogueira de Lira (Psico-USF, 2019)
This article gathered evidence of the validity of the Internalized Homophobia Scale (EHI) for Brazilian gays and lesbians. Study 1 found evidence of content validity (performed by two area judges and 10 gay and lesbian people), based on the internal structure and still sought reliability/precision indicators of the instrument. Based on an online survey, 261 participants, with a mean age of 27.6 years (SD = 7.72), answered IHS and sociodemographic questions. Study 2 replicated the factorial solution from study 1, through confirmatory factorial analysis, in addition to seeking complementary evidence of construct validity and reliability, being carried out with 303 gays and lesbians, with a mean age of 30.6 years (SD = 8.29). The results of the two studies suggest a modified version of the IHS with 19 items and two dimensions (Internal Perception of Stigma and Perception α = 0,814 of Social Oppression α = 0,622) because it presented evidence of validity and reliability/precision of the instrument.